Avaliação da distribuição superficial de potência de uma rede sem fio na banda de 5,8 ghz na região dos campos de petróleo do canto do amaro - Fialho, Bruno Rodrigues (2019)
Licensed free-range wireless communications networks have generally been intensified as research into the behavior of electromagnetic signal advertisements and the industry's interest in implementing these bands in telecommunications solutions and devices. The demand for new radiopropagation services is a factor of great importance in different procedures for the coverage prediction. In this context, the present work presents a fading analysis of the electromagnetic signals of a 5.8 GHz wireless network in a region of oil fields of the Bacia Potiguar, in the state of Rio Grande do Norte, called Canto do Amaro. Thus, the objective of this study is to evaluate the superficial and identifiable behavior as a shadow zone in the study environment. Field measurements were obtained, which were the necessary variables for the spatial interpolation methods, then from comparative tools compared with the Longley-Rice model measurement instruments. In order to obtain and evaluate the accuracy of the deterministic and geostatistical methods, the data sought by the mapping and cross - validation tests of the generated interpolation matrices were used. The results showed that the bending estimation method and the kriging method with scanning model is smaller than the average deviations of the mean error and that the coefficients of determination and correlation of Pearson are higher among the methods with the errors of the same. Therefore, statistical tools and an exploratory analysis of the data made it possible to compare results and measurements to evaluate wireless coverage and provide inputs for decision-making